2017
DOI: 10.1590/0102-778632120150053
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Extreme Climate Indices for Pará State, Brazil

Abstract: The present study aimed to analyze trends in air temperature and rainfall for 13 locations in the state of Pará using nonparametric tests. Daily data of maximum and minimum air temperatures and precipitation covering the period 1970-2006, collected by the Instituto Nacional de Meteorologia (INMET) have been used. From the results obtained it was observed that the number of warm days and nights per year has increased, thereby providing a significant reduction in the number of cool days and nights in the state. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
(22 reference statements)
0
8
0
3
Order By: Relevance
“…In order to investigate climatic indices in different regions of Brazil and South America, several studies have been performed (Santos and Brito, 2007;Santos et al, 2009;Satyamurty et al, 2010;Teixeira and Satyamurty, 2011;Skansi et al, 2013;Oliveira et al, 2017;Santos and Oliveira, 2017). However, most of these studies have focused on specific regions in AMZ or NEB and have not considered interregional differences.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate climatic indices in different regions of Brazil and South America, several studies have been performed (Santos and Brito, 2007;Santos et al, 2009;Satyamurty et al, 2010;Teixeira and Satyamurty, 2011;Skansi et al, 2013;Oliveira et al, 2017;Santos and Oliveira, 2017). However, most of these studies have focused on specific regions in AMZ or NEB and have not considered interregional differences.…”
Section: Introductionmentioning
confidence: 99%
“…This normative control restricts the boundaries and growth of the expansion of commercial crops, based on the trade-off that Honey production brings to the planning of the local rural economic development [37]. Adding to the threats to Honey production in the region, dos Santos and de Oliveira have found that temperatures in Para have risen in recent years and see the change in the natural landscape as the cause for the increased temperatures [40]. Clearing of the rainforests will increase the dry seasons [41], which harms the flora and, therefore, impacts the Honey production negatively [19].…”
Section: Quilombola Production and Logisticsmentioning
confidence: 99%
“…We use Pará from the Amazon biome as the targeted area of supply chain interventions and Tocantins from the Cerrado as the representative of the spillover system ( Figure 2), because these two states have experienced drastic land use changes and are in the agricultural frontiers in the two biomes. The area of Pará is 1,247,690 km 2 , 14% of the Brazilian territory (Santos and Oliveira, 2017) and 64% of which was covered by forest in 2015 (i.e., 794,383 km 2 of forest in 2015 based on INPE data). The population of Pará is 7.8 million in 2012, ranking ninth in the country.…”
Section: Applying the Telecoupling Framework To Deforestation In The mentioning
confidence: 99%